Power dependence of two-dimensional microstrip resonators for cellular filter applications. - Jenkins, A; Bramley, A; Hyland, D; Grovenor, C; Dew-Hughes, D; Edwards, D (1997)
Conventional microstrip linear (one dimensional) resonators suffer from high peak current density inside the resonators which limit the power handling characteristics. To realise higher power filters for cellular applications it is possible to use two dimensional microstrip resonators (such as disks) to equalise the internal current distribution. Such microstrip resonators have been designed and fabricated from TBCCO 2212 thin films deposited by RF sputtering onto 1cm square and 50mm diameter LaAlO3 substrates. The surface resistance of such films has been measured at 24 GHz using a sapphire dielectric resonator and shown to be less than 500 mu Omega scaled to 10 GHz and at 80K. Q values of 3-12 GHz disk resonators have demonstrated considerable improvements when compared to both linear HTS microstrip resonators and comparable copper disk resonators. Additionally, the power handling of such resonators has been shown to be superior to that of conventional linear resonators fabricated from similar material.